Informal Education Of Dharmika Women In Transforming Hindu Religious Values Toward Children In Banjar Tri Parartha Mataram City - Apriani, Luh (Widya Sandhi, 2024)
This study aims to examine informal dharmika women education in transforming Hindu religious values to their children at Banjar Parartha Perumnas Karang Permai, Sekarbela Subdistrict, Mataram City. This research was designed in a qualitative descriptive type using a case study model. Based on the results of this study it was found that the efforts of dharmika women in transforming Hindu religious values for their children in the family through several strategies. First, cooperation between husband and wife to be able to provide knowledge and at the same time be able to transform Hindu religious values for children in the family. Second, the husband and other family members must overcome the psychological pressures of dharmika so that later in carrying out the marriage ark they will feel happy. Third, studying Hinduism can be done through the internet and books about Hinduism also from members of the banjar. Fourth, directing their children to be more able to explore Hindu religious lessons at school, while the means of ceremonies and ceremonies as well as their implementation are self-taught.